Population Density and Habitat Preferences of Common Myna Acridotheres tristis (Aves: Sturnidae) in Selected Urban Areas in Kuching and Kota Samarahan, Sarawak - Ng, Wen Teng (Universiti Malaysia Sarawak (UNIMAS), 2017)
A study was carried out on the population density and habitat preferences of the invasive Common Myna (Acridotheres tristis) in selected urban areas in Kuching and Kota Samarahan. A total of321 individuals were detected throughout the three months sampling. Nine respective areas which comprised of 12 km line transects in total were employed in this study. Binoculars and range finder were used to collect data from 5 October 2016 to 13 December 2016, where DISTANCE was used to estimate the density of Common Myna. Observations on habitat preferences were tabulated using Microsoft Excel. Result reported that the population density of Common Myna in Area 1 (135.48 ± 31.333 individuals/km2 ) was the highest, and the lowest was Area 9 (23.841 ± 8.4148 individuals/km2). The availability offood sources and habitat were identified as the main factors that could affect the population density ofCommon Myna. Most ofthe Common Myna in selected areas were found roosting on the rooftop (60.25% in Kuching; 60% in Kota Samarahan), foraging on the ground (56.25% in Kuching; 87.1 % in Kota Samarahan) and nesting inside the rooftop (41.67% in Kuching; 66.67% in Kota Samarahan). This shows that Common Myna has high preference to forage on the ground, and roosting and nesting at a higher ground or structures to avoid predations and disturbances.